2009
DOI: 10.1037/a0015752
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent male rats exposed to social defeat exhibit altered anxiety behavior and limbic monoamines as adults.

Abstract: Social stress in adolescence is correlated with emergence of psychopathologies during early adulthood. In this study, we investigated the impact of social defeat stress during mid-adolescence on adult male brain and behavior. Adolescent male Sprague-Dawley rats were exposed to repeated social defeat for five days while controls were placed into a novel empty cage. When exposed to defeat-associated cues as adults, previously defeated rats showed increased risk assessment and behavioral inhibition, demonstrating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
190
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(218 citation statements)
references
References 77 publications
23
190
3
1
Order By: Relevance
“…Although this seems to be in contrast with some previous findings (Avital and Richter-Levin, 2005;Vidal et al, 2007;Watt et al, 2009;Buwalda et al, 2011), it does clearly indicate the relatively high resilience of adolescent rats to lastingly develop behavioral and neurobiological stress pathologies. More studies examining and comparing acute and long-term effects of social and non-social stressors at different developmental stages under social as well as non-social housing conditions in the framework of the match-mismatch hypothesis are warranted before definite conclusions can be drawn concerning the sensitivity of specific age groups with regard to stress and its long-term consequences.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Although this seems to be in contrast with some previous findings (Avital and Richter-Levin, 2005;Vidal et al, 2007;Watt et al, 2009;Buwalda et al, 2011), it does clearly indicate the relatively high resilience of adolescent rats to lastingly develop behavioral and neurobiological stress pathologies. More studies examining and comparing acute and long-term effects of social and non-social stressors at different developmental stages under social as well as non-social housing conditions in the framework of the match-mismatch hypothesis are warranted before definite conclusions can be drawn concerning the sensitivity of specific age groups with regard to stress and its long-term consequences.…”
Section: Discussioncontrasting
confidence: 55%
“…It is possible that the period between PND 35 and 42 represents a transition period during which adolescents move from one behavioral response to another and this could explain the lack of lasting behavioral changes in the present study. In another study applying social stress (Watt et al, 2009), it was shown that daily social defeat from PND 35 to 40 surprisingly caused a decreased anxiety in the elevated plus maze and an increased exploratory activity in the open field at PND 56. Only anxiety behavior in the context of the previous defeat stress increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, stress during childhood and puberty e termed hereafter as the peripubertal period e has been associated with psychopathology later in life (Heim and Nemeroff, 2001;Watt et al, 2009). The peripubertal period is a biological transitional phase involving adaptations in hormonal systems and neural circuits, including those related to stress and the development of emotionality (Spear, 2009;Romeo, 2010).…”
Section: Introductionmentioning
confidence: 99%